1996
DOI: 10.1144/gsl.sp.1997.119.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Environments of formation of ferromanganese concretions in the Baltic Sea: a critical review

Abstract: Ferromanganese concretions from the Baltic sea can be divided into three main types based on their abundance, morphology, composition and mode of formation; those from the Gulfs of Bothnia, Finland and Riga, from the Baltic Proper and from the western Belt Sea.Concretions from the Gulf of Bothnia are most abundant in Bothnian Bay where the abundance reaches 15-40 kg m -2 in an area of about 200 km 2. This is equivalent to about 3 million tonnes of concretions and has led to these deposits being evaluated as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 66 publications
(48 reference statements)
2
41
0
Order By: Relevance
“…Low sedimentation rates, erosional conditions, and seasonal redox cycling favor the formation of ferromanganese concretions at shallow water localities of the SW Baltic Sea (Glasby et al, 1997;Hlawatsch et al, 2002a). These Baltic Sea ferromanganese nodules show an onion-like growth pattern of alternating Fe-and Mn-rich layers.…”
Section: Introductionmentioning
confidence: 99%
“…Low sedimentation rates, erosional conditions, and seasonal redox cycling favor the formation of ferromanganese concretions at shallow water localities of the SW Baltic Sea (Glasby et al, 1997;Hlawatsch et al, 2002a). These Baltic Sea ferromanganese nodules show an onion-like growth pattern of alternating Fe-and Mn-rich layers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to controlling the Baltic Sea basin development, land uplift may exert profound influence on the cycles of particulate matter and of particle forming substances such as phosphorus (P). As the earth crust rises, more sediment areas are gradually exposed to the eroding force of wind and wave action (Jonsson et al 1990(Jonsson et al , 2003Glasby et al 1997;Meili et al 2000). Sediments of the Ö resund sound, which connects the Baltic Sea to the Kattegat, were once located above the sea level, but subsequently eroded down to bedrock during the course of 600 years, resulting in very high sedimentation rates in the adjacent Kattegat (Björck 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Sediments of the Ö resund sound, which connects the Baltic Sea to the Kattegat, were once located above the sea level, but subsequently eroded down to bedrock during the course of 600 years, resulting in very high sedimentation rates in the adjacent Kattegat (Björck 1995). More than 80% of the matter on the seafloor of the Baltic Sea emanates from eroded shallow sediments (Pustelnikov 1977;Jonsson et al 1990;Glasby et al 1997;Jönsson et al 2005). In comparison, primary production appears to have a more limited impact on deepwater sedimentation in the Baltic Sea, since more than 97% of the biogenic particles are mineralised in the water column before they reach the seafloor (Pustelnikov 1977;Emelyanov 1988;Glasby et al 1997;Trimonis and Stryuk 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They usually have a composition quite different from that of the surrounding material, and many are formed shortly after sediment deposition. Modern examples indude ferromanganese nodules (A> AGHA et al 1995;GLASBY et al 1996GLASBY et al , 1997 or siderite concretions found in salt marsh sediments (e.g. PYE et al 1990).…”
Section: Introductionmentioning
confidence: 99%